TINJAUAN LITERATUR : TELEMEDIKA SEBAGAI STRATEGI PELAYANAN KESEHATAN DI MASA PANDEMI DAN PASCA PANDEMI - Vivi Rizki Hensmit; Wulan Ervinna Simanjuntak; Purwadhi Purwadhi; Yani Restiani Widjaja (Journal of Innovation Research and Knowledge, 2024)
Telemedicine is a breakthrough in health services that allows interaction between medical personnel and doctors without meeting in person. The presence of telemedicine in health services is very beneficial during the COVID-19 pandemic when the physical distancing protocol is implemented. Telemedicine in the regulations set by the Indonesian government allows the implementation of telemedicine services that include consultation, diagnosis, therapy, and even monitoring. Telemedicine has the potential to be a solution to problems in Indonesia as a country with an uneven distribution of medical personnel and a doctor-to-community ratio that is still insufficient, so it is considered a good strategy for health services. The purpose of this study was to determine the benefits of telemedicine as a health service strategy during the pandemic and post-pandemic through a literature review. This study is a literature review obtained from the digital databases PubMed, Google Scholar, and Neliti with the keywords "telemedicine", "telemedicine", "e-health", "teleconsultation", "teleconsultation", "telehealth", and "Indonesia" which are adjusted to the inclusion and exclusion criteria. Based on the results of the study, 10 research articles from 2014-2024 were included. Telemedicine is a health service solution during the COVID-19 pandemic. In the post-pandemic era, telemedicine can still be an option for health services because it is still considered to have meaningful benefits